Implementing the Merdeka Curriculum in Primary Education: Evidence from Grade I and IV Teachers at Sungai Raya 01 Public Elementary School - Sri Nurjanah; Muhammad Asrori; Hairida (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
Purpose: This study examined Grade I and Grade IV teachers’ understanding, perceptions, planning, and classroom enactment of the Merdeka Curriculum at Sungai Raya 01 Public Elementary School, Indonesia. Method: A convergent mixed-methods case study was conducted from September 4 to October 23, 2024. Participants were six classroom teachers, including three Grade I teachers and three Grade IV teachers, selected through total sampling. Quantitative data were collected using a 25-item curriculum-understanding test, a 15-item perception questionnaire, and a structured classroom-observation instrument. Qualitative data were obtained through semi-structured interviews, field notes, and available teaching modules. Quantitative data were analyzed descriptively, qualitative data were analyzed thematically, and both strands were integrated through comparison. Main findings: Teachers achieved a mean understanding score of 83.67 and an overall perception score of 85.33%, both categorized as very good. External curriculum-related stimuli received the highest perception score at 93.33%, compared with individual understanding at 82.67% and individual evaluation at 82.22%. Classroom implementation scored 94.60%. Teachers prepared teaching modules under the supervision of the school principal, considered learning outcomes, used diagnostic assessment, and implemented student-centered and differentiated activities across introductory, core, and closing phases. However, technology-based instruction was not observed, and the formative use of assessment evidence was not fully documented. Novelty/originality: The study moves beyond single-source evaluations by distinguishing teachers’ knowledge, perceptions, reported planning, and observed practices within one integrated analytical framework. Contribution: It demonstrates that favorable perceptions and high scores do not necessarily indicate complete implementation. The findings provide contextual evidence for designing school-based professional development focused on differentiation, formative assessment, instructional technology, and stronger alignment between curriculum knowledge and classroom enactment in Indonesian primary education.